Pulsed Microwave Energy Transduction of Acoustic Phonon Related Brain Injury - Hubler, Graham K.; Hoffman, Stuart W.; Andreadis, Tim D.; DePalma, Ralph G. (Frontiers in Neurology, 2020)
Similarities between primary non-impact blast-induced mild Traumatic Brain Injury (mTBI) and recent clinical and imaging findings of unexplained brain injuries observed in US embassy personnel are possibly due to directed radiofrequency injury. The actual physical mechanisms causing brain damage are unexplained, while the clinical reality of these injuries remains controversial. Here we elucidate mechanisms, RF frequencies and power levels by which pulsed microwaves injure brain tissue. Physical theory and experimental data support the concept that pulse microwave injury and mTBI due to low-intensity primary blast injuries occur by acoustic phonon energy that causes ultrastructural subcellular injuries. Imaging to detect this injury requires specialized MRI; experimentally, transmission electron microscopy must be used to define subcellular injuries. We summarize the physical theory, injury mechanisms and microwave parameters to guide in vitro and in vivo investigations.